If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 3)(8n + 1) = 0 Reorder the terms: (3 + n)(8n + 1) = 0 Reorder the terms: (3 + n)(1 + 8n) = 0 Multiply (3 + n) * (1 + 8n) (3(1 + 8n) + n(1 + 8n)) = 0 ((1 * 3 + 8n * 3) + n(1 + 8n)) = 0 ((3 + 24n) + n(1 + 8n)) = 0 (3 + 24n + (1 * n + 8n * n)) = 0 (3 + 24n + (1n + 8n2)) = 0 Combine like terms: 24n + 1n = 25n (3 + 25n + 8n2) = 0 Solving 3 + 25n + 8n2 = 0 Solving for variable 'n'. Factor a trinomial. (3 + n)(1 + 8n) = 0Subproblem 1
Set the factor '(3 + n)' equal to zero and attempt to solve: Simplifying 3 + n = 0 Solving 3 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + n = 0 + -3 n = 0 + -3 Combine like terms: 0 + -3 = -3 n = -3 Simplifying n = -3Subproblem 2
Set the factor '(1 + 8n)' equal to zero and attempt to solve: Simplifying 1 + 8n = 0 Solving 1 + 8n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 8n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 8n = 0 + -1 8n = 0 + -1 Combine like terms: 0 + -1 = -1 8n = -1 Divide each side by '8'. n = -0.125 Simplifying n = -0.125Solution
n = {-3, -0.125}
| 7.5x^2-6x-9.8=0 | | -3j=7(-4j+20)+18j | | R-9=-5 | | -4(-7z+16)=7(3z+15)+20z | | -(9-3x)=11 | | 0.20(y-6)+0.06y=0.18y-0.03(30) | | -4-6k+6-8=-6-6k | | (2x)+3=(4x)-3 | | 8(4k+1)=15k+6(10k-13) | | 6t^2-26t+22=0 | | 0.75x+5y=20 | | 8x-3x^2+2x= | | 12x+20=-40 | | (-1x)+2=2+(-4x) | | -4s=-5(s-5) | | 4x^2+160=0 | | 24+x=54 | | (fg)(x)=(5x-2)(3x^2) | | 38+5x=-32 | | 6(x-4)+3x=5(2x+8)-14 | | 9x+7=7x+37 | | 12+4q+1=5(q+5) | | c+1-3=-21 | | .05t+.012(t+1)=.57 | | -4(17y-15)=-6(4+12y) | | 2(1.43)-y=7 | | G(5n)=2x^2-5 | | (-4x)+6=(-2x)+10 | | 20g-16=8(6g+19) | | -(5x-8)-(6x-3)+4=-6(x-4)-(9x+9)+3 | | 5x+(-2)=2x+10 | | -14.18-16.6v=-16.3v-9.68 |